Organizational Change Management in the Digital Transformation of Islamic Higher Education: An Analysis of Organizational Models and Strategies - Sharla Aulia Safana; Irawan; Afnie Rizky Nurkamaliyah; Chyril Futuhana Ahmad (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2026)
Islamic higher education institutions (Perguruan Tinggi Keagamaan Islam, PTKI) in Indonesia face mounting pressure to digitalize academic governance in response to Industry 4.0 and the Merdeka Belajar Kampus Merdeka (MBKM) policy, yet studies of the organizational change dimension of this process at regionally based institutions remain scarce. This study analyzes the strategies and organizational change models underlying digital transformation at Sekolah Tinggi Agama Islam (STAI) Al Falah Cicalengka, Bandung Regency. A qualitative case study design was used, drawing on direct observation, an in-depth interview with the institution's information technology (IT) team, and institutional and policy documents, analyzed through content analysis combined with the interactive model of Miles, Huberman, and Saldaña. Findings show that STAI Al Falah Cicalengka has implemented an integrated academic information system (SIAKAD) since 2019 and formed a dedicated IT team in 2023, reaching approximately 70% lecturer digital readiness; however, infrastructure constraints, uneven digital competence among senior faculty, and incomplete cross-unit system integration persist. Read through the Lewin, Kotter, and ADKAR frameworks, the institution has progressed through the unfreezing and changing stages and is moving toward refreezing, with strong awareness and desire for change but comparatively weaker ability and reinforcement. Islamic values integration remains largely an administrative add-on rather than a maqāṣid al-sharīʿah-based governance principle. The study contributes a values-integrated reading of established change-management models for regionally based Islamic higher education and offers practical recommendations a long-term digitalization roadmap, expanded server and hardware capacity, and structured digital-literacy training for strengthening sustainable organizational transformation.